Implementation of Earned Value Management in Unit-Price Payment Contracts - Picornell, M.; Pellicer, E.; Torres-Machí, C.; Sutrisna, Monty (ASCE, 2017)
The earned value management (EVM) method is internationally considered a standard tool in the project management field, enabling professionals to plan and control cost and schedule in an integrated manner. However, evidence indicates that EVM is not typically implemented by contractors when the payment agreement is based on unit-prices. In this payment approach, the owner pays the quantities actually executed according to the preagreed rate established in the contract for each unit or task; the income received by the contractor from the owner (generally named production) is neither proportional to costs nor fixed a priori, as in cost-reimbursable and lump sum contracts, respectively. Therefore, contractors have to control not only cost but also production. The current formulation of EVM does not allow controlling production; an additional baseline is needed. In response, this paper presents a proposal for adapting EVM to contractors when using the unit-prices payment agreement. Using a case study to illustrate, an additional baseline to account for production and profitability, as well as new indicators, is applied to allow contractors using EVM with this payment approach; this is the contribution of this paper to the body of knowledge. The proposed EVM formulation provides information not only in terms of cost (as in the traditional EVM approach) but also in terms of production.